Expression of survivin and p53 genes in patients with alopecia areata: A case–control study - Marie, Radwa El‐ Sayed Mahmoud; Abd El‐ Fadeal, Noha M; Atef, Lina M (Australasian journal of dermatology, 2021)
Background Alopecia areata is a common non‐scarring hair loss disorder. It has been generally recognised as a loss of immune privilege leading to an autoimmune attack upon anagen hair follicles. Survivin is one of the apoptosis inhibitor proteins, responsible for apoptosis suppression and cell cycle regulation. Survivin expression has been demonstrated in the matrix and outer root sheath keratinocytes of anagen hair follicles. Survivin overexpression was shown in several autoimmune diseases, and it was postulated that it contributes to the survival of self‐reactive T and B cells. P53 is a tumour suppressor gene that was suggested to repress autoimmunity via induction of T regulatory cells. Survivin gene expression is transcriptionally suppressed by wild‐type p53. Aim The aim of this study was to investigate survivin and p53 genes expression in alopecia areata patients. Methods The mRNA tissue expression of survivin and p53 was measured by quantitative real‐time polymerase chain reaction in lesional and non‐lesional punch scalp biopsies of 25 alopecia areata patients and 25 healthy subjects. Results The study showed higher mRNA expression of survivin in lesional biopsies compared to non‐lesional (P < 0.001) and control biopsies (P = 0.001). In non‐lesional biopsies, the expression was significantly lower than in control biopsies (P < 0.001). The expression of p53 was lower in both lesional and non‐lesional biopsies relative to control biopsies. However, the difference was only significant in non‐lesional biopsies (P = 0.017). Conclusion Our results suggested that survivin and p53 genes expression was altered in patients with alopecia areata.